Stringent response leads to continued cell division and a temporal restart of DNA replication after initial shutdown in Vibrio cholerae. Issue 6 (14th May 2019) - Kemter, Franziska S.; Schallopp, Nadine; Sperlea, Theodor; Serrania, Javier; Sobetzko, Patrick; Fritz, Georg; Waldminghaus, Torsten
Summary: Vibrio cholerae is an aquatic bacterium with the potential to infect humans and cause the cholera disease. While most bacteria have single chromosomes, the V. cholerae genome is encoded on two replicons of different size. This study focuses on the DNA replication and cell division of this bi‐chromosomal bacterium during the stringent response induced by starvation stress. V. cholerae cells were found to initially shut DNA replication initiation down upon stringent response induction by the serine analog serine hydroxamate. Surprisingly, cells temporarily restart their DNA replication before finally reaching a state with fully replicated single chromosome sets. This division‐replication pattern is very different to that of the related single chromosome model bacterium Escherichia coli . Within the replication restart phase, both chromosomes of V. cholerae maintained their known order of replication timing to achieve termination synchrony. Using flow cytometry combined with mathematical modeling, we established that a phase of cellular regrowth be the reason for the observed restart of DNA replication after the initial shutdown. Our study shows that although the stringent response induction itself is widely conserved, bacteria developed different ways of how to react to the sensed nutrient limitation, potentially reflecting their individual lifestyle requirements. Abstract : Vibrio cholerae is an aquatic bacterium with the potential to infect humans. This study focuses on the DNA replication and cell division of this bi‐chromosomal bacterium during starvation stress. Surprisingly, cells temporarily restart their DNA replication after a first shut down period before finally reaching a state with fully replicated single chromosome sets.